Manufacture of synthetic nitric acid - Ofiana, Oscar; Perez, Librada; Reyes, Cecilia (Diliman, Quezon City College of Engineering, 1961)
A plant having a capacity of 50 tons of 58% nitric acid per day can supply the demand. A plant of this size will involve a total capital investment of 1,145,454. It was found out that the total annual cost is 111,500 for which the unit cost price of the product is 64.70 per ton. To be able to operate the plant profitably, we have to sell the product at 70 per ton, for which we can have an annual income of 21,000.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plnts; Nitric acid